Feed supplementation during the last third of gestation: effects on ewes and lambs up to weaning - Moura Filho, José; Ribeiro, Edson Luis de Azambuja; Silva, Leandro das Dores Ferreira da; Rocha, Marco Antonio da; Mizubuti, Ivone Yurika; Pereira, Elzânia Sales; Mori, Rinaldo Masato (Semina: Ciências Agrárias, 2005)
The objective of this work was to verify the effects of feed supplementation with concentrate during the last third of gestation on ewes and lambs explored for meat production up to weaning. Fifty-three adult Hampshire and Ile de France ewes with their lambs were used in this experiment. Ewes were divided in two groups: T1 (without supplementation) and T2 (supplemented with 250 g of a mixture of 75% of grounded corn and 25% of soybean meal). Animals were maintained on Coastcross pasture and received 2.0 kg of sorghum silage every day. The collected data from ewes were: Weights at beginning of the breeding season, at the beginning of supplementation and at lambing; from lambs it was collected weights at birth and at every 14 days up to weaning. Supplemented ewes presented greater body condition scores at lambing than non-supplemented ewes, however supplementation did not affect body weight at lambing. Furthermore, supplemented ewes had smaller weight losses during the last third of gestation. Supplementation of ewes affected the birth weight of lambs, but did not influence the other weights, weight gains and mortality of lambs up to weaning. Six teeth ewes were heavier than four and eight teeth ewes during the whole experimental period. Eight teeth ewes presented greater twin lambing rates and a greater mortality of lambs than six teeth ewes. There were no differences in the performance of the lambs of the two genetic groups. It was concluded that the feed supplementation allowed a better body condition to ewes at lambing, however, it did not affect the lamb production up to weaning.